A Novel Inter and Intra Routing Algorithm - Sharma, P; Prabadevi, B (International Journal of Computer Sciences and Engineering, 2025)
Routing algorithm plays a vital role in any NETWORK communications. The purpose of algorithm is to make a connection between the hops. Though different routing algorithms coexist for inter routing and intra routing but still there is need for the better one, so we make deep analysis on the existing algorithms and propose a new algorithm. The analysis addresses various routing algorithm issues and a method to overcome them. The parameters taken for comparison include speed, interconnection with the other algorithm and we develop an algorithm which will work in both inter and intra routing environment. The study analysis the functionality of the routing protocol in the real network by designing it using Gns3. Also it discusses the problems faced by the admin of the network by examining how it works in the real environment.